Analysis of Pesticides in Tomato Combining QuEChERS and Dispersive Liquid–Liquid Microextraction Followed by High-Performance Liquid Chromatography - Melo, Armindo (2013)
A new sample preparation procedure combining QuEChERS and dispersive liquid–liquid microextraction (DLLME) was optimized for the determination at trace levels of 13 pesticides from different chemical families (i.e. 2,4-D, acetamiprid, bentazone, cymoxanil, deltamethrin, dicamba, diuron, foramsulfuron, mesotrione, metalaxyl- M, methomyl, pyraclostrobin and tembotrione) in tomato by high-performance liquid chromatography with diode array detection. Target pesticides from tomato samples were isolated by liquid partitioning with acetonitrile and salts and cleaned up by dispersive solid-phase extraction (d-SPE); the analytes were concentrated in trichloromethane by the DLLME procedure. The disperser solvent from DLLME was used at the same time as carrier of analytes form extraction in QuEChERS method. The main factors affecting sample cleanup by d-SPE in QuEChERS and DLLME yield were optimized by means of an experimental design.Under the optimum conditions, good linearity was obtained, the recoveries of pesticides in tomato samples at spiking levels between 0.01 and 1.00 mg/kg ranged from 86 to 116 % (for foramsulfuron and cymoxanil, respectively). Precision was within 15.0 % (RSD) except at the LQ for tembotrione, which was 17.4 %. Limits of quantification achieved (ranging from 0.0058 to 0.15 mg/kg) were below the maximum residue limits established by the European Union.